Lignées féminines et dynamiques Égypte-Syrie-Iraq au début de l’époque marwanide - Marie Legendre (Revue des Mondes Musulmans et de la Méditerranée)
This article offers to re-examine a number of conclusions in the recent publication of J. Mabra on the governorate of ‘Abd al-‘Azīz b. Marwān in Egypt (65/685-86/705). The book offers an account of the tribal alliances that allowed the Marwanids to access to the califate as well as an examination of some of the dynamics between ‘Abd al-Malik (65/685-86/705) and his governors of Egypt and Iraq. J. Mabra understands the administration of ‘Abd al-‘Azīz as independent from the caliphal centre in Damascus and opposed to his brother’s reform on language use and coinage. After reconsidering the reading of a number of papyrus documents, coins and narrative sources, it is offered here to see the appointment of such a governor as one of the keys to the Marwanid success and to reject the idea that caliphal ruling strategies aimed at centralizing the Umayyad realm.